LINK AND MATCH PENDIDIKAN KEJURUAN DENGAN DUNIA USAHA DAN INDUSTRI DI INDONESIA - Irwanto Irwanto (Jurnal Inovasi Penelitian, 2021)
The purpose of this study is to determine the link and match in vocational education collaboration with the business and industry in Indonesia. In the cooperation that exists between vocational education with the business world and the industrial world, it cannot be separated from the role of school collaboration with the community. The SMK has an important task to create a cooperation and benefit. In this research, using qualitative research and descriptive approaches. The data source in this study used informants at SMKN 4 Serang city and industry. Types of data collection used in this study include observation, interviews and documentation. Analysis of the data used in the study using an interactive model from Milles & Huberman. The results of the study indicate that link and match planning through the vocational education relationship program with the business world and the industrial world has been implemented at SMKN 4 Serang city, namely industrial practices, training, industrial visits, and recruitment of outstanding alumni. The implementation of establishing school cooperation includes the procedures for implementing partnerships with the business world and the industrial world at SMKN 4 Serang city.